2011
DOI: 10.5194/acp-11-4657-2011
|View full text |Cite
|
Sign up to set email alerts
|

VOC reactivity and its effect on ozone production during the HaChi summer campaign

Abstract: Abstract. Measurements of ozone and its precursors conducted within the HaChi (Haze in China) project in summer 2009 were analyzed to characterize volatile organic compounds (VOCs) and their effects on ozone photochemical production at a suburban site in the North China Plain (NCP). Ozone episodes, during which running 8-h average ozone concentrations exceeding 80 ppbv lasted for more than 4 h, occurred on about two thirds of the observational days during the 5-week field campaign. This suggests continuous ozo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 51 publications
4
68
0
Order By: Relevance
“…This shows the nonlinear nature of tropospheric photochemistry. In agreement with recent East Asian megacity studies in China and Japan (Wang et al, 2008;Bao et al, 2010;Ran et al, 2011;Geng et al, 2011), observations and model simulations at the TRF site in South Korea demonstrate the importance of natural VOC emissions in regional photochemistry near megacities. The presented observational and modeling results also show that the TRF site near the edge of the Seoul Metropolitan Area is suitable for investigating anthropogenic and biogenic interactions including VOCs and reactive nitrogen compounds (e.g.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This shows the nonlinear nature of tropospheric photochemistry. In agreement with recent East Asian megacity studies in China and Japan (Wang et al, 2008;Bao et al, 2010;Ran et al, 2011;Geng et al, 2011), observations and model simulations at the TRF site in South Korea demonstrate the importance of natural VOC emissions in regional photochemistry near megacities. The presented observational and modeling results also show that the TRF site near the edge of the Seoul Metropolitan Area is suitable for investigating anthropogenic and biogenic interactions including VOCs and reactive nitrogen compounds (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…Bao et al (2010) presented a 3-D photochemical modeling study of regional ozone production, in the Kinki region of Japan, with and without BVOC photochemistry and concluded that BVOC emissions from the suburban area can significantly contribute to ozone enhancement in the urban region. Ran et al (2011) showed VOC measurement results from a suburban site near Beijing and Tianjin, China in the summer of 2010. Although their site is downwind of two megacities, their analysis indicates that biogenic isoprene (C 5 H 8 ) was the second most dominant OH sink among all of the VOC species measured in the afternoon when photochemistry is very active.…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the literature results with the inclusion of heterogeneous reaction (Liang et al, 2013b;Wu et al, 2015), but notably shorter than the recent studies conducted by Khan et al (2015) and Nguyen et al (2015) without the coupling of the heterogeneous process. Although dry deposition is thought to dominate the atmospheric lifetime of peroxides in previous studies (Reeves and Penkett, 2003), its role in the lifetime of atmospheric peroxides is insignificant during Wangdu Campaign 2014. The sensitivity of modeled relative loss of dry deposition to the uncertainties in the planetary boundary layer height was low as the contribution of dry deposition to the loss of H 2 O 2 in Phase I decreased no more than 10 % with the PBL height doubled.…”
Section: Heterogeneous Uptake Of Peroxides By Aerosolmentioning
confidence: 99%
“…In the NCP, it has been revealed that the vehicular exhaust is the predominant source responsible for the VOC species such as propene, trans/cis-2-butene and trimethylbenzene in the surrounding areas of the observation site (Yuan et al, 2009;Ran et al, 2011;Wu et al, 2016), while the vegetation governs the release of isoprene. It is recommended to take measures for vehicle emission control and land use management (e.g., modifying the amount and types of vegetation) in order to mitigate the pollution of atmospheric peroxides in the NCP Figure 5.…”
Section: Peroxide Simulationmentioning
confidence: 99%
See 1 more Smart Citation